Acquired Sleep-Related Hypermotor Epilepsy with Disrupted White Matter Tracts Assessed by Multishell Diffusion Magnetic Resonance Imaging - Tchopev, Zahari N.; Yeh, Ping-Hong; Morgan, Greg W.; Meyer, Eric; Wolf, Johanna M.; Ollinger, John M.; Riedy, Gerard P.; Young, Lisa C. (Frontiers in Neurology, 2018)
Sleep-related hypermotor epilepsy (SHE) (previously frontal lobe epilepsy) is a rare seizure disorder commonly misdiagnosed or unrecognized, causing negative patient sequelae. While usually reported in familial studies, it is more commonly acquired. Diagnosis is a challenge due to its low incidence in comparison to the more common sleep disorders or psychogenic etiologies in the differential diagnosis. Diagnosis is scaled on degree of certainty based on described or clinically documented semiology, with video EEG as a helpful, but not necessary, adjunct. Current treatment is similar to other focal epilepsies. We studied a 36-year-old active duty male soldier who presented with two years of predominantly sleep related, abrupt, short, anamnestic hyperkinetic movements with unstructured vocalizations. Prior work-up included non-contributory video electroencephalography (EEG) and polysomnography (PSG) as well as normal brain magnetic resonance imaging (MRI). Treatments for presumed psychiatric and parasomnia disturbances were not effective in establishing diagnosis or relief. Evaluation at our tertiary, multi-disciplinary care institution recorded events consistent with the diagnosis of clinical SHE. He was enrolled in an advanced multi-shell diffusion weighted imaging (DWI) MRI research study to evaluate white matter tracts, given his history of mild, repetitive, non-penetrating traumatic brain injuries (TBI), not otherwise requiring hospitalization. Multishell diffusion MRI tractography found changes not previously described in the right frontal lobe white matter tracts. These changes were consistent with neurological localization and serve as a potential nidus for this patient’s seizure disorder. Misdiagnosis of SHE can result in detrimental biopsychosocial sequelae of untreated epilepsy, unnecessary or harmful intervention, or the stigmata of a behavioral disorder. Further investigation into diagnosis and etiology of acquired SHE is needed. Assessment for white matter abnormalities can potentially provide information into pathogenesis of epilepsy disorders.